Feminist Insiders-Outsiders Muslim Women in Nigeria and the Contemporary Feminist Movement. - Uthman, Ibrahim Olatunde (Newcastle upon Tyne : Cambridge Scholars Pub., 2009)
This book examines different brand of women's feminist struggles and focuses on the struggles of Muslim women who are insiders in the Islamic Movement, as represented in Nigerian Muslim women's Islamic activism. Drawing on different secular-Islamic Gender feminist theoretical frameworks, the book closely analyses Islamic texts and these Muslim women brand of feminism, which reflect the effects of their strong Islamic commitment culture on their gender relations, postulations and feminist stru ...
Table of contents; preface; acknowledgements; chapter one; chapter two; chapter three; chapter four; chapter five; chapter six; bibliography; appendix a; appendix b.
Description based on print version record.
Keywords: Muslim women -- Nigeria -- Social conditions; Muslim women -- Political activity -- Nigeria; Feminism -- Religious aspects -- Islam; SOCIAL SCIENCE / Women's Studies; Electronic books